A facile method to pattern silver nanowires on sandpaper and its application in pressure sensors. (20th February 2023) - Wang, Li; Geng, Yang
Abstract: A conductive layer deposited on a rough surface can effectively improve the performance of a pressure sensor; however, its further application requires patterning of the conductive layer to obtain the corresponding electrical layout. In this paper, a facile patterning method with few steps was proposed for patterning silver nanowires on sandpaper. This method employed a photocurable resin as the key material to define the pattern using a photomask under UV exposure. It was found that greater cure depths and narrower light-transmitting areas require longer exposure times. A pattern with linewidth of approximately 40 μ m was obtained on M-400 sandpaper (M-400 stands for the mesh number). Based on this method, pressure sensors consisting of interdigital electrodes with rough surfaces and sponge-sensing layers were fabricated. The best resulting sensor exhibited a high-pressure sensitivity of 21.89 kPa −11 for less than 2 kPa, a low detection limit (24.5 Pa), low operating voltage (0.01 V), and short response time (84 ms). Moreover, this patterning method has no special requirements for materials and substrates and thus can be applied to pattern other materials on rough or smooth surface substrates.